Peran Permainan Edukatif dalam Meningkatkan Minat Belajar Matematika Siswa Sekolah Dasar - Debby Yuliana Sinaga; Desvita Sari; Nurmala Agustina Siahaan; Dian Sri Rezeki Sirait; Septiani Saragih; Agnes Gita Sonia Sihombing; Bintari Saragih; Jennifer Demi Arta Simamora; Yunika Lamtiur Purba; Hotmaida Sinaga (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
One essential component of human life is education,resource development, and mathematics plays an essential role in developing logic and problem-solving skills among students. However, many elementary school students find mathematics to be difficult and boring, resulting in a lack of interest in the subject. One solution to enhance interest in learning is through the use of educational games. This study aims to analyze the role of educational games in improving elementary school students' interest in learning mathematics. The method employed is a literature review, collecting and analyzing related references. The findings suggest that the use of educational games can increase student motivation and learning outcomes by creating an enjoyable and interactive learning environment.